Pelatihan Penulisan Artikel Ilmiah di Sekolah Tinggi Agama Islam Al-Karimiyah, Depok, Jawa Barat - Fitria Ayuningtyas; Drina Intyaswati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Scientific articles have always been a very important topic because they are an important part of science. The community service team seeks to provide scientific article writing training to help guide writing scientific articles for students who are preparing their thesis. Based on the results of observations and discussions on the undeveloped ability to write and publish student scientific articles and have not been socialized and various problems related to student learning activities, it is possible to identify various problems in the field, namely given examples of articles in the library or other campus facilities for reading and student reference. To overcome the problems mentioned above, the implementation of solutions to these problems, the team provided a webinar through Google Meet about writing scientific articles and the publication process for students of STAI Al-Karimiyah, Department of Islamic Education. The team shared information about the writing of scientific articles and the publication process in the planned journal. The result of this community service is that students are expected to be able to write scientific articles according to the journal standards.